A surprising abundance of massive quiescent galaxies at 3 < z < 5 in the first data from JWST CEERS. Issue 3 (2nd February 2023) - Carnall, A C; McLeod, D J; McLure, R J; Dunlop, J S; Begley, R; Cullen, F; Donnan, C T; Hamadouche, M L; Jewell, S M; Jones, E W; Pollock, C L; Wild, V
ABSTRACT: We report a robust sample of 10 massive quiescent galaxies at redshift, z > 3, selected using the first data from the JWST Cosmic Evolution Early Release Science programme. Three of these galaxies are at 4 < z < 5, constituting the best evidence to date for quiescent galaxies significantly before z = 4. These extreme galaxies have stellar masses in the range log10 ( M * /M⊙ ) = 10.1–11.1, and formed the bulk of their mass around z ≃ 10, with two objects having star formation histories that suggest they had already reached log10 ( M * /M⊙ ) > 10 by z ≳ 8. We report number densities for our sample, demonstrating that, based on the small area of JWST imaging so far available, previous work appears to have underestimated the number of quiescent galaxies at 3 < z < 4 by a factor of 3–5, due to a lack of ultra-deep imaging data at λ 2 μ m. This result deepens the existing tension between observations and theoretical models, which already struggle to reproduce previous estimates of z > 3 quiescent galaxy number densities. Upcoming wider-area JWST imaging surveys will provide larger samples of such galaxies and more robust number densities, as well as providing opportunities to search for quiescent galaxies at z > 5. The galaxies we report are excellent potential targets for JWST NIRSpec spectroscopy, which will be required to understand in detail their physical properties, providing deeper insights into the processes responsible for forming massive galaxies and quenching star formation during the first billion years.